Therapeutic targeting of VEGF and/or TGF-β to enhance anti-PD-(L)1 therapy: The evidence from clinical trials - Li, Linwei; Wen, Qinglian; Ding, Ruilin (Frontiers in Oncology, 2022)
Normalizing the tumor microenvironment (TME) is a potential strategy to improve the effectiveness of immunotherapy. Vascular endothelial growth factor (VEGF) and transforming growth factor (TGF)-β pathways play an important role in the development and function of the TME, contributing to the immunosuppressive status of TME. To inhibit VEGF and/or TGF-β pathways can restore TME from immunosuppressive to immune-supportive status and enhance sensitivity to immunotherapy such as programmed death protein-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) inhibitors. In this review, we described the existing preclinical and clinical evidence supporting the use of anti-VEGF and/or anti-TGF-β therapies to enhance cancer immunotherapy. Encouragingly, adopting anti-VEGF and/or anti-TGF-β therapies as a combination treatment with anti-PD-(L)1 therapy have been demonstrated as effective and tolerable in several solid tumors in clinical trials. Although several questions need to be solved, the clinical value of this combination strategy is worthy to be studied further.